Geochronology, geochemistry, origin, and tectonic implications of high‐pressure mafic granulites of the Amdo region, Central Tibet. Issue 11 (2nd June 2020) - Xie, Chaoming; Song, Yuhang; Duan, Menglong; Su, Li; Hao, Yujie
Abstract : The Amdo Terrane, Central Tibet, was previously located in the middle of the Bangong–Nujiang Ocean (BNO), and is key to understanding the subduction history of the BNO. However, the high‐pressure (HP) mafic granulites of the Amdo Terrane remain poorly studied. Here, we report the petrology, geochemistry, and zircon U–Pb geochronology of the Amdo HP mafic granulites. The granulites occur mainly as enclaves or deformed dikes in granitic gneisses of the Amdo Terrane. Zircons from the granulites yield two clusters of ages, at 193–192 and 180 Ma. The former represents the best estimate of the age of peak metamorphism, and the latter represents the age of retrograde amphibolite‐facies metamorphism. Although the contents of mobile elements in the granulites, including the large‐ion lithophile elements (Rb, Sr, Cs, Pb, K), were significantly altered during metamorphism, the contents of the high‐field‐strength elements (HFSEs; Th, Nb, Zr, Ti) and rare earth elements (REEs) remained largely unchanged. The granulites belong to the tholeiitic basalt series, with SiO2 contents of 47.05–51.03% and Mg# of 35–50. The REE contents of the granulites are characterised by flat chondrite‐normalised patterns (LaN /YbN = 0.96–1.92; LaN /SmN = 1.0–1.59) and weak Eu anomalies (Eu/Eu* = 0.84–0.99). Most of the granulite samples have high TiO2 contents, clear negative Nb and Ta anomalies, and high Pb enrichment, with positive zircon ε Hf ( t ) values (+8.14 to +16.02). The granulites exhibit both normal mid‐ocean ridge basalt (N‐MORB) and island‐arc basalt (IAB) characteristics. Using the data presented here and previous data, we suggest that the protolith of the granulites were back‐arc basin basalts derived from high‐degree partial melting of depleted mantle in the spinel stability field, which records the early evolution of the BNO. Northward subduction of the BNO oceanic plate led to back‐arc spreading and the formation of back‐arc basin basalts on the northern margin of the Amdo Terrane. The back‐arc basin extended further to form an ocean basin, which separated the Amdo Terrane and the Southern Qiangtang–Baoshan (SQB) Terrane, resulting in the Amdo Terrane becoming an isolated microcontinent in the BNO.